Does Enterprise Resource Planning (ERP) Impact on Earnings Quality? - Jovita, First Tania Putri; Wedari, Linda Kusumaning (Jurnal Ilmiah Akuntansi dan Bisnis, 2024)
With some benefits of Enterprise Resource Planning (ERP) implementation in improving data accuracy, efficiency, governance and decision support, it is assumed that it can improve the earnings quality. This study aims at examining the impact of ERP implementation on earnings quality of manufacturing listed companies on the Indonesia Stock Exchange during period 2018-2021. The earnings quality is measured by the absolute value of discretionary accruals the Kothari Model (2005). Of 484 observations, the results showed that ERP implementation has a significant positive impact on earnings quality. This finding may contribute to literature as empirical evidence of the ERP system's effectiveness. These results particularly indicate that ERP implementations enhance the quality of financial reporting by constraining opportunistic managerial behaviour. In addition, understanding this underlying benefit can help firms in choosing investments and actions to effectively improve earnings quality. Keywords : enterprise resource planning (ERP), earnings quality, discretionary accruals